A Critical Review of the Policy on Child Placement in Military Barracks: The Perspective of Islamic Law and Child Protection in Indonesia - Isnaini, Luluk Nur; Billah, Ana (Al Mashaadir : Jurnal Ilmu Syariah, 2025)
The rising phenomenon of juvenile delinquency in Indonesia such as brawls, alcohol consumption, and violence against teachers and parents has prompted several local governments to implement a policy of placing problematic children in military barracks. This policy aims to discipline children instantly but raises debates about its legal basis, psychological impact, and conformity with child protection principles. This study critically analyzes the policy of placing children in military barracks from the perspectives of national law, Islamic law, and child protection, and explores its implications for reforming the child rehabilitation system. The research employs a qualitative approach with normative legal analysis of statutory regulations, literature reviews, and document studies from child protection agencies. The findings indicate that the military barracks policy lacks a clear legal foundation, contradicts the best interests of the child principle, and carries a high risk of long-term psychological trauma. From an Islamic law perspective, the policy is inconsistent with the principles of maqāṣid al-sharīʿah, which emphasize education through compassion, gradual guidance, and exemplary conduct. This study recommends reformulating child rehabilitation policies into a community-based, humane, and collaborative model aligned with national and international child protection standards.